2020
DOI: 10.1525/elementa.00044
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of epifaunal communities in the Hudson Bay system

Abstract: The seasonal sea ice cover and the massive influx of river runoff into the Hudson Bay System (HBS) of the Canadian Arctic are critical factors influencing biological production and, ultimately, the dynamics and structure of benthic communities in the region. This study provides the most recent survey of epibenthic communities in Hudson Bay and Hudson Strait and explores their relationships with environmental variables, including mean annual primary production and particulate organic carbon in surface water, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…Similar results were observed in a previous study where epibenthic assemblages on the continental shelf of the Canadian Arctic were most dissimilar near the Mackenzie River (Roy et al, 2014). In Hudson Bay, assemblages showed low biodiversity values and high dissimilarity near the Nelson River Estuary (Pierrejean et al, 2020). A metadata analysis by Cusson et al (2007) also identified salinity as one of the most important variables that explained patterns in benthic biodiversity and assemblage composition in the Canadian Arctic.…”
Section: Influence Of Local Variablessupporting
confidence: 88%
“…Similar results were observed in a previous study where epibenthic assemblages on the continental shelf of the Canadian Arctic were most dissimilar near the Mackenzie River (Roy et al, 2014). In Hudson Bay, assemblages showed low biodiversity values and high dissimilarity near the Nelson River Estuary (Pierrejean et al, 2020). A metadata analysis by Cusson et al (2007) also identified salinity as one of the most important variables that explained patterns in benthic biodiversity and assemblage composition in the Canadian Arctic.…”
Section: Influence Of Local Variablessupporting
confidence: 88%
“…Most of the scientific knowledge of RWS and the ice bridge arises indirectly from study of the polynya and associated biological communities. The polynya in RWS is commonly associated with the much larger polynya in western Hudson Bay (Landy et al, 2017;Bruneau et al, 2021), which is known to be highly productive (Barbedo et al, 2020;Pierrejean et al, 2020;Matthes et al, 2021). While there are no published in situ observations of productivity in RWS, strong tidal mixing is believed to generate hotspots of nutrient-rich surface waters particularly at the northern end of the sound (C.J.…”
Section: Scientific and Historical Knowledge Of Rws And The Ice Bridgementioning
confidence: 99%
“…In a more recent study, Piepenburg et al (2011) compiled observations for the same area, giving a total of 463. Furthermore, Pierrejean et al (2020) found a total of 380 epibenthic taxa identified which represents 71% of the estimated taxa within the Hudson Bay. Finally, Wei et al (2020) identified the Hudson Complex (including James Bay) as one of the six hotspots of diversity among the 13 ecoregions around Canada.…”
Section: Marine Macrobenthosmentioning
confidence: 99%